Filtered decision feedback channel estimation for OFDM-based DTV terrestrial broadcasting system - Chini, A.; Yiyan Wu; El-Tanany, M.; Mahmoud, S. (IEEE transactions on broadcasting, 1998)
Orthogonal frequency division multiplexing (OFDM) is one of the transmission techniques used for digital television (DTV) terrestrial broadcasting. A high quality channel estimator with a low training overhead is the key to the successful delivery of DTV services which require high spectrum efficiency and robustness to strong and dynamic ghosts. Robustness to multipath distortion is especially important in a single frequency emission environment. This paper presents an application of a filtered decision feedback channel estimator for OFDM-based DTV systems using high order QAM modulations. The implementation and the performance of the channel estimator are discussed. Computer simulations were conducted to evaluate the performance of the channel estimator. The channel estimation loss is about 1.2 dB from the ideal case where the channel is assumed to be known by the receiver. For a given multipath spread, the loss can be further reduced by increasing the FFT size. The FFT size is however subject to an upper limit imposed by the Doppler spread.